The Coaching of Immature Morals Child by Religious Activities - Suwartiningsih, Suwartiningsih; Besari, Anam (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
The purpose of this study was to find out how adolescent moral development through religion in mosques, to find out the form of adolescent moral development through religion in mosques, to find out what obstacles the ustadz had about how to build youth character through religion in mosques. This research is motivated by first, it appears that the lack of education in the field of religion, secondly, they often carry out activities that are outside the teachings of Islam, thirdly, many of these teenagers do not carry out the obligations that Allah has commanded in Religion. It can be seen that the behavior of these adolescents can be seen in everyday life who tend to rarely do the obligatory prayers, when sunset time comes they are still enjoying playing. The method used in this research is descriptive qualitative method, and the type of research used is field research (field recearch). Sources of data from this study consisted of primary data, namely: the head of the mosque, and secondary data, namely: adolescents. While the data collection techniques used were observation and interviews, the data that had been collected were then processed by data reduction, data presentation and drawing conclusions. The results showed that the morality of the adolescents in Desa Budug Kwadungan Kabupaten Ngawi. After carrying out positive activities about religion such as the presence of recitation, the adolescents did more positive things, and it could even be said that the adolescents had quite good morals.